2007
DOI: 10.1080/01480540601186929
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Evaluation of Paracetamol Effects in Human Lymphocytes Culture

Abstract: Paracetamol is a common analgesic and antipyretic drug. It has been recognized as one of the most ordinary medications taken in overdoses. We examined the possible genotoxic effects of high paracetamol concentrations expected to occur after overdose. Paracetamol was added to the cultures at the beginning of the cultivation period. Separate cultures for three tested concentrations of paracetamol (50 microg/mL, 100 microg/mL, and 200 microg/mL) were set. Effects of paracetamol were evaluated by micronucleus cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Immunological disturbances were demonstrated only in the case of acetaminophen‐induced liver injury caused by toxic doses, 23 or in the presence of coexisting lymphoma 24 . Overdose has been linked to genotoxic effects in human peripheral blood lymphocytes, 25 and acetaminophen may enhance the risk of developing leukemia 26 . In any case, enrolled subjects neither surpassed the daily limit dose of this analgesic, nor showed any abnormality in routine blood liver function tests.…”
Section: Commentsmentioning
confidence: 92%
“…Immunological disturbances were demonstrated only in the case of acetaminophen‐induced liver injury caused by toxic doses, 23 or in the presence of coexisting lymphoma 24 . Overdose has been linked to genotoxic effects in human peripheral blood lymphocytes, 25 and acetaminophen may enhance the risk of developing leukemia 26 . In any case, enrolled subjects neither surpassed the daily limit dose of this analgesic, nor showed any abnormality in routine blood liver function tests.…”
Section: Commentsmentioning
confidence: 92%
“…In contrast, at higher concentrations (> 200 µg/ml), the genotoxic impact, as well as its antiproliferative activity, have been proven. 4,11,12 Reviewing the results of some research on the cytotoxicity and genotoxicity of paracetamol, the diversity of the research results, including the differences in the in vivo and in vitro behavior of paracetamol, leads to the conclusion that there is no clear or established way of its behavior as a cytotoxic and genotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…Paracetamol increases the frequency of chromosomal damage in mammalian cell lines, isolated human lymphocytes, and experimental animal studies. 4 Two independent studies showed increased chromosomal damage in human lymphocytes after taking therapeutic doses of paracetamol, while a third study gave negative results. The inhibition of ribonucleotide reductase probably causes paracetamol-induced chromosomal damage, indicating that a given dose of paracetamol may induce a threshold level for chromosomal damage.…”
Section: Introductionmentioning
confidence: 99%